How disruptive is 5G?. (September 2018) - Cave, Martin
Abstract: The hypothesis is put forward that, after three decades of stability, there is now the prospect of significant change in the vertical and horizontal structure of the mobile market place. On the supply side, significant factors are, first, the availability of a new and very powerful form of mobile connectivity in the shape of 5G, and second, software defined networking, which allows a single network to provide a variety of heterogeneous services or 'slices'. On the demand side, the digital transformation of the whole economy (and not just the communications sector) creates the need for diverse communications functions operating in a universe with a much wider set of digitally transformed services. Mobile operators will find themselves contesting customer relationship with firms or other organisations providing these services in an integrated fashion, and thus risk replacing their direct link with end users with becoming the wholesale supplier of an expanded but 'commoditised' communications product. We may also observe fewer radio access networks; more competitive backhaul; and the (partial) vertical disintegration of mobile network operators. The regulatory changes implied may include heavier regulation of fewer RANs, and the need for market analyses to confront situations in which network operators sell more and more of their services to a variety of heterogeneous content and application providers – some of them exercising substantial levels of market power. Highlights: 5G will be introduced in age of digital transformation and network virtualisation. This combination will change the horizontal and vertical structure of the mobile sector. Regulation will have to change to match increased concentration in radio access networks.